Wawrzyniec Grzymała Goślicki - życie i działalność - Stępkowski, Aleksander (Prawo Kanoniczne, 1999)
The article is sacrificed to the person of Wawrzyniec Grzymała Goślicki (Laurentius Grimaldus Goslicus), senator and bishop of Poland, author of the political treaties De optimo senatore. The treaties is one of less known in Poland, but was very popular in England, where it was published in English three times (The Counsellor [1598], A Comonwealth of good counsaile [1607], The Accomplished Senator [1733]). We do knowalso that the treaty was twice plagiarised, first in Germany as Jurisprudentiae Politicae, apud Antonium Hummium (1611), second one was The Sage Senator published in England (1660). There is also a manuscript of English translation of the first book of the treaties (1585). There are other evidences of its popularity in England and western Europe. In USA the treaties is considered as influencing authors of Declaration of Independence and Constitution of USA. Reprint of The Accomplished Senator was published in USA in 1992. The most probable date of his birth is 1538 in Goślice near Płock. He studied at Jagiellonian University theology and liberal arts (1556-1562). Than hewas continuing his education in Padua and Bologna studying theology, philosophy, oratory, Greeks, astronomy and law, finishing it as utrisque iuris doctor. It was stressed that he was one of the most educated person in Poland. As humanist he was not only political writer but also splendid orator and poet, writing in Latin. After his return to Poland Goślicki acts in the Royal secretary, proceeding many diplomatic missions. Simultaneously he is member of hierarchy of Catholic Church in Poland. In 1587 he entered Senat as a bishop of Kamieniec, than Chełm (1590), Przemyśl (1591), Poznań (1601). As bishop he had been introducing reforms of Tridentina. In 1593 with few persons was preparing Union of Brześć on the ground of which the orthodox hierarchy returned to Catholic Church. In politics Goślicki was acting as mediator between conflicting parties. Died in 1607 in Ciążyń preparing synod in Poznań. His sepulchre is in Cathedral in Poznań.